As matrizes curriculares do curso de Licenciatura em Matemática da Universidade Federal de Santa Maria: discussões sobre a formação inicial do professor - Golin, Ana Luiza (2021)
This master's thesis refers to an investigation carried out within the concentration area of Mathematics Education and the research line: Teaching and Learning of Mathematics and its Philosophical, Historical and Epistemological Foundations of the Graduate Program in Mathematics Education and Teaching of Physics at the Federal University of Santa Maria (PPGEMEF/UFSM). The research aims to investigate elements in the curriculum matrices of the Licentiate Degree in Mathematics at the Federal University of Santa Maria that express historically changes in the initial training of teachers. To contemplate this objective, this study was guided by the theoretical assumptions of the Historical-Cultural Theory (THC) and those about curriculum and initial teacher education. It was constituted through theoretical-bibliographic and documental investigation through two main stages: 1) survey and study of the National Curriculum Guidelines (DCN) for teacher training and for Mathematics Courses; and 2) analysis of the curricular matrices of the Licentiate Degree in Mathematics at UFSM since its implementation. As a data source, the National Curriculum Guidelines and the curricular matrices of the Course implemented in the years of: 1979, 1995, 2001, 2005, 2013 and 2019 were used. From the data systematization, it was decided to analyze them through nine categories, eight of them listed in the studies by Gatti et al. (2008): 1) Theoretical Foundations; 2) Knowledge Relating to Educational Systems; 3) Specific Knowledge of the Area; 4) Specific Knowledge for Teaching; 5) Knowledge Relating to Specific Teaching Modalities; 6) Other Knowledge; 7) Research and Course Conclusion Work; 8) Complementary Activities and 9) Internships. For this purpose, the following elements that make up the subjects of the curricular matrices were taken into account: semesters, nomenclatures, longer and shorter hours, difference between hours, number of courses offered, workload for the practical and theoretical part, total workload and menus. The results obtained indicate: the drastic decrease in the percentage referring to the category of Specific Knowledge of the Area, although it still concentrates the greatest part of it; the considerable increase in the percentage related to Specific Knowledge for Teaching and Internships, indicating that the disciplines belonging to these categories gained more attention during the reformulations; the inclusion and exclusion of several disciplines and the presence of disciplines related to other areas of knowledge aiming at a broader education. The study of the constitutive elements of the Curriculum Matrices allowed us to understand that they reveal a model of training a subject to exercise an activity - teaching -, being part of the humanization process, as they express the knowledge considered relevant to be appropriated for the future teacher. The changes that have occurred historically in the organization of the matrices of the studied course were influenced by legislation, economic, political and social aspects, determining the ways of thinking of those who organized them about what would be important for teacher education, and are noticeable in the direction of valuing the knowledge related to the teacher's work: teaching.